An Act Prescribing Additional Penalties for the Commission of Offences against the State, and for Other Purposes, Ch. 1460, No. 3, § 14, 1865 Fla. Laws 23, 25-27. - (:unkn) unknown (General Publisher, 1866)
That if any negro, mulatto, or other person of color, shall intrude himself into any religious or other public assembly of white persons, or into any railroad car or other public vehicle set apart for the exclusive accommodation of white people, he shall be deemed to be guilty of a misdemeanor, and upon conviction, shall be sentenced to stand in the pillory for one hour, or be whipped, not exceeding thirty-nine stripes, or both, at the discretion of the jury; nor shall it be lawful for any white person to intrude himself into any religious or other public assembly of colored persons, or in to any railroad car or other public vehicle, set apart for the exclusive accommodation of persons of color, under the same penalties.
--
Keywords: CARRY - CERTAIN PUBLIC PLACES